Potencial empreendedor, estratégia e porte da empresa: um estudo no setor metal-mecânico - Morais, Ulisses de Souza (2008)
The objective of this study was to evaluate the relationship between entrepreneurial potential and the strategy classification of Miles and Snow, as well as the relationship between these two variables and firm size. The data was collected by means of an instrument comprising the two studied models and was applied among controllers of firms of Curitiba and Metropolitan Region associates to the SINDIMETAL (Union of the Metallurgic, Mechanical Industries and of Electric Material of the State of the Paraná). Entrepreneurship in this academic research is a combination of some traits commonly mentioned as characteristics of entrepreneurs like need for achievement, risk-taking and innovation propensity and strategic posture. These traits were combined in an instrument of research named Carland Entrepreneurship Index – CEI in order to offer a score to classify individuals as macro-entrepreneur, entrepreneur and micro-entrepreneur. The entrepreneurial potential measured through the CEI has as premise the assumption that everyone is an entrepreneur. And the strategy, in this study, follows the model developed by Miles and Snow, that categorize four types of strategy: the prospector, the defensive, the analytical and the reactive. Ninety and seven from a total of three hundred fifty seven metallurgic, mechanical firms and of electric material from Curitiba and Metropolitan Region were investigated. The design of this research can be classified as formal, interrogative, ex-post-facto, descriptive, cross-sectional, and quantitative. The results permitted to state that, in this study and for the business area investigated, the prospector strategy was adopted by the controllers; there is no association between entrepreneurial potential and strategy and between firm size and the type of strategy. However, there is a relationship between entrepreneurial potential and firm size. The study contributed towards a better understanding of the relationship between entrepreneurial potential, strategy and firm size, since its results had not differed from previous ones.